Distribution and Controlling Growth Factors of Ooids in Qinghai Lake, Northern Tibet Plateau, China - Hao, Lewei; Tao, Huifei; Li, Shutong; Ma, Xiaofeng; Ji, Hongjie; Qiu, Junli (Frontiers in Earth Science, 2022)
Ooids are coated carbonate grains which exist in shallow water marine and laccustrine environments. There is an ongoing debate about whether the origin of ooids is inorganic or organic. Qinghai Lake is the largest inland lake in China, and ooids on the lake shore. This paper focuses on whether environmental energy has an impact on the growth and size of ooids. Through hydrochemical analysis, thin section observation, and scanning electron microscope, the carbonate coats of beach sands from Qinghai Lake were studied. The research shows that the carbonate coated grain content from the different shores of the lake present variations. The hydrodynamics and particularly the waves seem to control the distribution of carbonate coats in the lake shore not the hydrochemical condition. In addition, the integrity and thickness of carbonate coats from the shores with strong hydrodynamic force are high and thick, respectively. The carbonate coats are often observed on medium grained sands and the maximum carbonate coated grain occurred under the strongest waves, indicating that ooids can be produced only when hydrodynamic force and particle size are well matched. Bacteria or extracellular polymeric substances (EPS) are not observed within the ooid cortices by scanning electronic microscopy (SEM). So, bacteria may be not a major factor in the formation and growth of ooids, but hydrodynamic forces appear to play a great role in carbonate grain coat distribution, integrity, thickness, and ooid grian size.